Are Risk Factor Disclosures Still Relevant? Evidence from Market Reactions to Risk Factor Disclosures Before and After the Financial Crisis - Beatty, Anne; Cheng, Lin; Zhang, Haiwen (Contemporary Accounting Research, 2019)
ABSTRACT The SEC's Disclosure Effectiveness Initiative (December 2013) highlights a difference between accounting regulators and academics in their perceptions of Item 1A risk factor disclosure effectiveness. Because most academic evidence relies on pre‐financial crisis data, we compare changes in risk factor disclosure informativeness before and after the crisis as a possible explanation for this disconnect. We further explore this discrepancy by considering (i) three classes of market participants, (ii) new, discontinued, and repeated disclosures, and (iii) nonmarket outcomes. Our results confirm previous findings but indicate that those results no longer hold in the subsequent period. Specifically, we find that although equity, option, and bond markets react to unexpected risk factor disclosures in the period leading up to the financial crisis (2006–2008), the market reactions decline significantly in the post‐crisis period (2009–2014). Perhaps surprisingly, the documented changes in informativeness are not driven by disclosures repeated from one year to the next but instead result from new disclosures initiated in the current year and, in the option and debt markets, also from disclosures discontinued from the previous year. Finally, using the Altman Z ‐score as an objective bankruptcy risk measure, we find that the association between risk factor disclosures and companies’ future bankruptcy risk declines significantly in the post financial crisis period. Taken together, these findings contribute to the current disclosure effectiveness debate by highlighting that risk factor disclosures, which were informative in the preceding period, become less reflective of the underlying economic risks and thus less informative to investors in the post‐crisis period. La déclaration des facteurs de risque est‐elle toujours pertinente ? Données tirées des réactions du marché à la déclaration des facteurs de risque avant et après la crise financière